Anti-inflammatory and Anti-proliferative Diterpenes from Croton stellatopilosus Ohba - Charoenwong Premprasert (Prince of Songkla University, 2024)
Thesis (Ph.D., Pharmaceutical Sciences)--Prince of Songkla University, 2019